2011
DOI: 10.2500/ajra.2011.25.3630
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Chronic Rhinosinusitis in Korea

Abstract: Although the prevalence and risk factors vary according to time, place, and diagnostic criteria, periodic epidemiological study on CRS is necessary to reduce socioeconomic expenditure and establish an improved national health care policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
70
2
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(83 citation statements)
references
References 22 publications
(36 reference statements)
8
70
2
3
Order By: Relevance
“…It is estimated that CRS affects up to 10 % of the population in the USA, with similar prevalence estimates in Europe and Asia [46]. Interestingly, few studies have evaluated the frequency of patients with CRSsNP compared to those who have CRSwNP in the general population.…”
Section: Epidemiologymentioning
confidence: 99%
“…It is estimated that CRS affects up to 10 % of the population in the USA, with similar prevalence estimates in Europe and Asia [46]. Interestingly, few studies have evaluated the frequency of patients with CRSsNP compared to those who have CRSwNP in the general population.…”
Section: Epidemiologymentioning
confidence: 99%
“…in a recently published review article but are further summarized in our discussion and in Table 2. [5, 6**, 45**, 46, 47**, 48]…”
Section: Comorbid Diseases and Conditions Associated With Crsmentioning
confidence: 99%
“…[51] Other larger population-based studies have found strong associations between AR and comorbid CRS although the timing of the AR diagnosis relative to CRS onset was not elucidated (Table 2). [5, 46] In the study by Kim et al ., the aOR of having CRS among patients with moderate-severe persistent AR was 8.2 when compared to mild intermittent AR. One limitation of epidemiologic studies of AR and CRS is that the symptoms of these two conditions overlap substantially and may be difficult to differentiate using a questionnaire.…”
Section: Airway Diseasesmentioning
confidence: 99%
“…Bei kritischer Analyse der Literatur lässt sich feststellen, dass eine geringe Septumdeviation [9,192] keinen Einfluss auf die Häufigkeit einer CRS besitzt, während Deviationen > 3 mm in einigen Untersuchungen mit einer erhöhten Prävalenz assoziiert sind [193,194], in anderen jedoch nicht [192,195,196]. Entsprechend kann erklärt werden, warum eine koreanische Untersuchung die Septumdeviation nicht als Risikofaktor nachgewiesen hat [9], um in einer aktuelleren Untersuchung im gleichen Land Widerspruch zu finden [98]. Nahezu gleiche Verteilungen von CRS-Patienten und Gesunden wurden für eine paradoxe Biegung des Proc.…”
Section: Sinu-nasale Anatomische Variationenunclassified